Two-stage valve homogenisation enhances particle dispersion in milk protein concentrates during reconstitution and reduces heat-induced particle aggregation in resultant dispersions - Hebishy, Essam; Le Berre, Marianne; Crowley, Shane V.; O’Mahony, James A. (Frontiers in Food Science and Technology, 2022)
Milk protein concentrates (MPCs) are highly functional ingredients, with high-protein variants increasingly used in numerous applications. The objective of this study was to determine the impact of homogenisation, as part of the rehydration process, on solubility and heat stability of MPC. An 80% protein MPC powder was reconstituted (3% protein, w/v) and homogenised at 50°C using a pilot-scale, two-stage, valve homogeniser at different total pressures of 0, 5, 10, 15 and 20 MPa. Rehydrated samples were analysed for solubility, particle size, protein profile and heat stability (change in particle size distribution on heating in an oil bath at 140°C for 5 min). The results showed a considerable increase in solubility after applying homogenisation at 5 MPa. Homogenisation at pressures of 5–10 MPa reduced particle size of MPC dispersions further, with further increases in pressure having no additional effect. Increased heat stability was observed on increasing homogenisation pressures up to 10 MPa. This work demonstrates the positive impact of homogenisation on particle dispersion in MPCs and identifies a possible link between improved dispersion and heat stability. This would be applied as a strategy in dairy plants to reduce fouling in heat surfaces which suggests a significant economic impact in dairy processing.